Transcriptomic Profiling of Human Placental Trophoblasts in Response to Infection with Enterococcus faecalis - Qianglai Tan; Feng Xu; Hengyi Xu; Liang Qiu; Xueying Tao; Hua Wei (Journal of Food Quality)
Increasing evidence suggests that Enterococcus faecalis strains can pass through placental barriers and cause adverse outcomes during pregnancy. However, the underlying molecular mechanism of the interaction between E. faecalis and the host placental barrier has yet to be fully elucidated. In this study, we have used DNA microarray analysis to investigate the response of human placental trophoblast-like BeWo cells to infection with E. faecalis OG1RF. These results indicate that a total of 2191 genes in BeWo cells are differentially expressed in the presence of E. faecalis OG1RF, with 1357 genes being upregulated and 834 genes being downregulated. These differentially expressed genes (DEGs) are involved in apoptosis, stress and stimulus response, placental and embryonic development, immune response, and cell adhesion. Therefore, these results provide information on the molecular mechanisms that E. faecalis invasion can trigger to cause adverse pregnancy outcomes.